2002
DOI: 10.1088/0963-0252/11/2/303
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of a wafer interface of a pulsed two-frequency capacitively coupled plasma for oxide etching by emission selected computerized tomography

Abstract: We have carried out emission selected computerized tomography time and space measurements of the absolute net production rate of Ar(2p 1 ) in a pulsed capacitively coupled plasma for SiO 2 etching pulsively sustained at 100 MHz and continuously biased at 500 kHz between electrodes in CF 4 /Ar and pure Ar at 25 mTorr. Double-layer formation by excessive negatively charged particles in the interface close to the wafer is experimentally estimated only at the wafer's anodic phases during the off-period of the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The control of plasma properties in these applications is of primary importance. During the last couple of years it has been recognized that the plasma maintenance and ion properties may be controlled independently from each other using plasma sources excited by two different radio frequencies [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of plasma properties in these applications is of primary importance. During the last couple of years it has been recognized that the plasma maintenance and ion properties may be controlled independently from each other using plasma sources excited by two different radio frequencies [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The flux and energy distribution of the ions interacting with the electrode (target) surfaces is of primary importance. Understanding the details of ion properties is the motivation of the present study, in which we investigate discharges in Ar, CF 4 and their mixtures, the latter being used in the etching of silicon and silicon-dioxide. One should bear in mind that recently Turner and Chabert [12] have given a deeper understanding of the interaction between the two plasma sources and their effect on the mechanism of electron heating.…”
Section: Introductionmentioning
confidence: 99%
“…Additional interesting results in the research of production and properties of negative ions in Ar/CF 4 can be found (for example, in [10][11][12]). …”
Section: Introduction and State Of The Artmentioning
confidence: 93%
“…[4][5][6] In the recent years, the characterization of multi-frequency rf discharges has retained the attention of many authors. Optical emission spectroscopy and diagnostic measurements [7][8][9][10][11][12] have been performed in capacitive and inductive configurations. The complications introduced by multiple rf sources were focused by several numerical models.…”
Section: Introductionmentioning
confidence: 99%